Dynamics and Structural Characteristics of Inflation in Bulgaria - Velichkov, Nikolay (Research Papers, 2024)
The paper examines the dynamics and structural characteristics of inflation in Bulgaria in 2022 – 2023. Within the framework of the analysis, various structural sections of inflation are made. They refer to the decomposition of the overall harmonised index of consumer prices into individual consumer groups at different levels of disaggregation. Along with the analysis of the price behaviour of these groups of goods and services over time, their contributions to the general inflation in the country are also assessed. The obtained empirical results show the presence of certain specificities in the course of the inflationary process and its structural characteristics. These features reflect determining factors of the price dynamics in Bulgaria during the studied time period.
Keywords: Inflation; HIPC